2005
DOI: 10.1111/j.1365-2141.2005.05371.x
|View full text |Cite
|
Sign up to set email alerts
|

Difference in absolute risk of venous and arterial thrombosis between familial protein S deficiency type I and type III. Results from a family cohort study to assess the clinical impact of a laboratory test‐based classification

Abstract: SummaryHereditary protein S (PS) deficiency type I is an established risk factor for venous thromboembolism. Contradictionary data on type III deficiency suggests a difference in risk between both types. We studied 156 first degree relatives (90% of eligible relatives) from type I deficient probands (cohort 1) and 268 (88%) from type III deficient probands (cohort 2) to determine the absolute risk of venous and arterial thromboembolism. Annual incidences of venous thromboembolism were 1AE47 and 0AE17 per 100 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 28 publications
5
47
1
1
Order By: Relevance
“…32 As the nAPCsr is a marker of the risk of venous thrombosis, 36 the data presented in Figure 3C support the outcome of the Kaplan-Meier analysis and confirm that type I and type III PS deficiencies confer similar risks of thrombosis. This finding is in line with that from a previous study, 22 but contrasts with data from other studies in which the risk of thrombosis associated with type III PS deficiency was found to be half that associated with type I deficiency 23 or not elevated at all. 21 A possible explanation for these discrepancies may be the population selection criteria, as it has been reported that type III deficient individuals from families with pure type III deficiency are not at risk of thrombosis, while those from mixed type I/type III deficient families are.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…32 As the nAPCsr is a marker of the risk of venous thrombosis, 36 the data presented in Figure 3C support the outcome of the Kaplan-Meier analysis and confirm that type I and type III PS deficiencies confer similar risks of thrombosis. This finding is in line with that from a previous study, 22 but contrasts with data from other studies in which the risk of thrombosis associated with type III PS deficiency was found to be half that associated with type I deficiency 23 or not elevated at all. 21 A possible explanation for these discrepancies may be the population selection criteria, as it has been reported that type III deficient individuals from families with pure type III deficiency are not at risk of thrombosis, while those from mixed type I/type III deficient families are.…”
Section: Discussioncontrasting
confidence: 57%
“…Currently, type I PS deficiency is generally considered a risk factor for venous thrombosis, while conflicting results have been reported for type III deficiency. [21][22][23] In the present study we re-evaluated the thrombosis risk associated with type I and type III PS deficiencies by Kaplan-Meier analysis of a large cohort of PS-deficient families. Our data indicate that hereditary type III PS deficiency is a risk factor for venous thrombosis and that it confers a similar risk as type I PS deficiency (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatives were tested for factor V Leiden, prothrombin G20210A, and hereditary deficiencies of antithrombin, protein C and protein S by methods described previously. [15][16][17] To avoid bias, probands were excluded from the analyses. The study was approved by the institutional review boards of the participating hospitals.…”
Section: Design and Methodsmentioning
confidence: 99%
“…[13][14][15][16][17] Between May 1998 and July 2004, first-degree relatives aged 15 ABSTRACT years or older of consecutive patients (probands) with documented venous thrombosis (i.e. deep vein thrombosis or pulmonary embolism) or any documented arterial thrombosis before the age of 50 years, were enrolled after obtaining informed consent.…”
Section: Design and Methodsmentioning
confidence: 99%